The Effect of Different Stocking Densities on Life and Absolute Weight Growth of Gurami Fish Fingerlings (Osphronemus gouramy) - Budiyanto, Didik; Wirawan, Indra; Kustiana, Melinda (Jurnal Media Akuakultur Indonesia, 2024)
Gouramy has long been cultivated by fish breeders in Indonesia, but there are still many obstacles faced by these fish breeders, namely the very slow growth rate when compared to other freshwater fish. One effort to find out the factors that affect the slow growth rate of fish, among others, is to treat the stocking density of fish seeds. Not much is known about the optimal stocking density for gouramy seeds. This study aims to determine the effect of different stocking densities on survival and growth in absolute weight of gourami (O. gouramy) fry. The method used was using RAL (Completely Randomized Design), using 4 treatments, 6 replications. The results showed that the survival rate for treatment A gave the highest yield of 91.6% and the highest weight gain was found in treatment A with the highest yield of 3.87 grams. The water quality of all treatments during the study showed a decent and good enough range for the growth of gouramy, namely the pH ranged from 7.56 – 7.61, the temperature ranged from 26.1 – 26.2°C, and the DO ranged from 5.19 – 5.29 ppm.